PERANCANGAN SISTEM INFORMASI POSYANDU BERBASIS WEBSITE PADA POSYANDU CEMPAKA 1 DESA PASIR JAMBU BOGOR - Rosa Helvida Errendyar (2022)
In this digital era, data management is easy to do anywhere and anytime. Posyandu which is one of the activities in the health sector, seeks to improve health in order to provide convenience in obtaining health services. One of them is the provision of free health services every month to monitor the nutritional status and health conditions of infants and toddlers, as well as providing immunizations. The importance of this can reduce the risk of stunting. In the implementation of posyandu activities, new child data is recorded, weighing data, immunization data, calculation of the age and nutritional status of children, and reporting between posyandu cadres and village midwives. However, these activities are still carried out manually, making it difficult for posyandu cadres and hampering the reporting process to village midwives. In overcoming this, the author built a system using the waterfall method and UML visual modeling, which was built using the CodeIgniter framework and MySQL database. The results of this study are a website-based information system that can manage data, as well as calculate the age and nutritional status of children automatically, whether malnutrition, less, good, or more, and also reporting becomes easier, faster, precise, effective and efficient on Posyandu Cempaka 1 Pasir Jambu Village, Bogor.